Formazione e mobilità nel GIS: il progetto VESTA-GIS - Salvemini, Mauro; Belardi, Laura; Di Donato, Pasquale; Mercadante, Valeria (GEOmedia, 2009)
Training e mobility in GIS: the VESTA-GIS project VESTA-GIS is a network aimed to set up a context for enhancing professional skills in the changing labour market consequent to the ever increasing importance of GI in the favourable and continuously evolving framework of the new European Directives for environment and territory. The Directive is currently dealing with problems that have reached a new European dimension (i.e. INSPIRE) which have strong impact on the methodologies used in the GI Community. VESTAGIS is committed both to improve the GIS skills existing on the market and to promote mobility of people.